Analisis Faktor-Faktor Niat Beli Ulang dalam Pembelian Online - Ryan Fahmi Hikmat (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Research on repurchase intentions needs to be re-done to get the latest conditions regarding market conditions for marketers and find out consumer developments in strengthening in-depth arguments for themselves until they finally make a decision to repurchase. This study adapts a theory of reasoned action as a basis for knowing consumer behavior. Behavior according to Theory of Reasoned Action (TRA) is influenced by intentions, and intentions are influenced by subjective attitudes and norms. This attitude is influenced by beliefs about the results of the actions that have been taken. Subjective norms are influenced by beliefs about the opinions of others and the motivation to follow those opinions. In conclusion, this theory explains that a person will take an action if he sees the action as positive and if he believes that other people want him to follow it. Until now, studies related to re-purchase intentions are still relevant to be examined, given the need for an appropriate model to explain how a perception of value and trust affects consumers' buying intentions. This research presents a model of relationship of perception of value and belief to re-purchase intention with risk variables as moderation variable. The target of respondents in this study are the students, because according to the researchers the perpetrators of online buying and selling activities are mostly students who have understood very well about the use of technology in online transactions.